My Personal Evolution of Caring for Patients with Congenital Cleft Malformations: A Joyous, but Humbling Career - Sykes, Jonathan M.; Nolen, David (Facial Plastic Surgery, 2014)
The evaluation and treatment of patients with congenital orofacial clefting is a challenging task. Successful treatment requires a concerted effort by the cleft surgeon and cleft team to maximize the appearance and function of the cleft patient. To become a competent cleft surgeon, a facial plastic surgeon must be dedicated to a lifelong pursuit of technical excellence through continual evaluation, self-criticism, and improvement of surgical techniques and approaches. The contemporary cleft surgeon must integrate the knowledge gained by mentors that have years of expert experience and evidence-based information demonstrated by careful study. This information should help guide the young cleft surgeon as experience is gained and expertise developed through years of careful observation and evaluation of patients. This article is a discussion of the art and science of cleft surgery. It outlines the timetable associated with cleft repairs, the resources necessary to provide superior cleft care, and exposes the weaknesses and frailties of all cleft surgeons. It is designed to aid cleft surgeons in their pursuit of perfection.
Keywords: cleft tip; cleft palate; cleft rhinoplasty; orthognathic surgery; cleft deformity